Special Care Dentistry Curriculum at The Undergraduate Level : Students’ Prespective - Fuad, Natrah A.; John, Jacob; Koh, Wen T.; Mani, Shani A.; Lim, Wan-Lin S.; Wong, Chee S.; Joshi, Vinod K.; Rohani, Maryani M.; Zwetchkenbaum, Samuel (Journal of Dentistry Indonesia, 2015)
Special needs patients (SNP) have diffculty accessing dental services, partly due to reluctance of dentists to treat them. Objective: We assess didactic and clinical training experiences of fnal-year dental students and new graduates in managing SNP. Methods: An online questionnaire was sent to 123 fnal year dental students and new graduates, assessing their experiences and readiness in handling SNP. Results: Majority of the respondents were not confdent in attending to SNP. Majority gained knowledge in handling SNP via lectures while more than half had managed patients with complex medical history. Majority mentioned a lack of clinical training to treat SNP as their dental training experience had only been in a dental school clinical setting. Most of the respondents hope their curriculum would include more education to improve clinical skills in managing SNP. Conclusion: Respondents demonstrated minimum training and lack of confdence and skills that might contribute to a lack of preparedness to manage the oral health care needs of SNP. Clinical exposure in managing SNP at the undergraduate level is still inadequate and it needs to be emphasized in the curriculum